Prediction of periapical status and tooth extraction. (23rd December 2015) - Kirkevang, L. –L.; Ørstavik, D.; Bahrami, G.; Wenzel, A.; Væth, M.
Abstract: Aim: To describe and analyse risk factors associated with prediction of periapical status, assessed using the full‐scale Periapical Index (PAI) supplemented with extraction as outcome variable. Methodology: In 1997–1998, 616 randomly selected individuals from Aarhus County, Denmark, underwent a full‐mouth radiographic survey. All 616 were re‐invited in 2003–2004 and in 2008–2009, when 473 and 363 persons, respectively, consented and attended a new radiographic examination. The study population of the present investigation included 330 persons who had participated in all three examinations, and 143 persons who had participated in the first and second examination only. Using the full‐mouth radiographic survey and interview information, the following variables were assessed: on person level – age, gender, smoking habits and number of teeth; on tooth level – presence of tooth, PAI, root filling, caries, marginal bone level, restoration, jaw and tooth group. The outcome variable was the 5 score PAI supplemented with extraction. The observation period was 5 years. Ordered logistic regression analyses were carried out for root filled and non‐root filled teeth separately. The Regional Committee of Ethics approved the study. Results: For both root filled teeth and non‐root filled teeth, the baseline PAI score was the most important predictive factor of periapical status and extraction ( P < 0.0001). Non‐root filled teeth had in general a better outcome than root filled teeth. However, in non‐root filled teeth, several other factors had a significant influence on the outcome, and the risk estimates were larger and showed a more pronounced variation between the different categories of predictive factors. For root filled teeth few variables, other than baseline PAI score, influenced the outcome significantly. Conclusion: The full‐scale PAI was the strongest predictive factor of periapical status or extraction even when adjusted for additional factors, such as marginal bone level. A high baseline PAI score increased the risk for an impaired outcome. The large difference in risk estimates for non‐root filled compared to root filled teeth documents the importance of separate analyses/studies for identification and quantification of predictive factors associated with periapical status and extraction of a tooth.